LC-MS/MS analysis of phosphatidylethanol in dried blood spots versus conventional blood specimens - Stadler, Andrea; Richter, Barbara; Kluge, Matthias; Koenig, Patrick; Seitz, Helmut K.; Thierauf, Annette; Gnann, Heike; Winkler, Michaela; Mattern, Rainer; Skopp, Gisela (Analytical and bioanalytical chemistry, 2011)
Phosphatidylethanol (PEth), which is formed extrahepatically by the action of phospholipase D on phosphatidylcholine in the presence of ethanol, has been suggested as a promising marker of alcohol misuse. Analysis of dried blood spots (DBS) is particularly advantageous for the determination of delicate analytes such as PEth. Therefore, measurement of PEth species (18:1/18:1, 16:0/18:1) in DBS versus whole blood was performed to ascertain whether respective results are directly comparable. Samples were obtained from subjects (n = 40) undergoing alcohol detoxification treatment. Analysis involved liquid-liquid extraction from both, DBS and whole blood (100 μL, respectively), with phosphatidylpropanol as the internal standard. Extracts were subjected to LC gradient separation using multiple reaction monitoring of deprotonated molecules. Results from measurements of corresponding DBS and whole blood specimens were compared by estimating the respective mean values and by a Bland and Altman analysis. Concentrations of PEth 18:1/18:1 ranged from 46.1 to 3,360 ng/mL in whole blood (mean, 461.7 ng/mL) and from 35.8 to 3,360 ng/mL in DBS (mean, 457.6 ng/mL); for PEth 16:0/18:1, concentrations were from 900 to 213,000 ng/mL (mean, 23,375 ng/mL) and 922-213,000 ng/mL (mean, 23,470 ng/mL) in blood and DBS, respectively. Estimated mean differences were −4.3 ng/mL for PEth 18:1/18:1 and 95.8 ng/mL for PEth 16:0/18:1. The Bland-Altman plot of both PEth species showed that the variation around the mean difference was similar all through the range of measured values and that all differences except one were within the limits of agreement. It could be shown that the determination of PEth species in DBS is as reliable as in whole blood samples. This assay may facilitate monitoring of alcohol misuse.